2019
DOI: 10.12688/f1000research.14978.2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors contributing to parenting styles: A systematic review

Abstract: Background: The set of strategies used by parents to put their children’s behaviors under control are called parenting styles, which can be influenced by numerous factors including socio-economic variables, cultural differences, personal characteristics, and psychological factors. These factors can differently contribute to parenting style. The purpose of this systematic review was to examine psychological factors affecting parenting style. Methods: This study was a comprehensive literature review using the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
13
0
1
Order By: Relevance
“…Regarding the effects on parental practices, covariance analyses showed that maternal depression had predictive value for the presence of more negative practices when the effects of the sex of the children were controlled, and for relaxed discipline and inconsistent punishment practices. These findings corroborate a review on parenting styles, which indicates that the mother's mental health status is a significant risk factor for the increase in negative behaviors in relation to children (Vafaeenejad et al, 2018). These results also draw attention to the presence of multiple adverse variables of the family context that, combined, impact child development.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the effects on parental practices, covariance analyses showed that maternal depression had predictive value for the presence of more negative practices when the effects of the sex of the children were controlled, and for relaxed discipline and inconsistent punishment practices. These findings corroborate a review on parenting styles, which indicates that the mother's mental health status is a significant risk factor for the increase in negative behaviors in relation to children (Vafaeenejad et al, 2018). These results also draw attention to the presence of multiple adverse variables of the family context that, combined, impact child development.…”
Section: Discussionsupporting
confidence: 86%
“…In Brazil, major depressive disorder mainly affects adult women living in urban areas (Lopes, Hellwig, Silva, & Menezes, 2016), many of whom are of childbearing age and/or are mothers. Thus, living with depressive symptoms in the family environment can be considered a condition of adversity for children, as indicated by the systematic review by Vafaeenejad, Elyasi, Moosazadeh, and Shahhosseini (2018), which found that the mental health of parents is one of the main factors affecting family interactions and the childcare condition, making clear the presence of competing adverse variables for child development.…”
mentioning
confidence: 99%
“…Therefore, it appears that there are perhaps other variables besides parent and child characteristics that influence the parenting styles. This may be explained by findings of a recent meta-analysis, 57 which found that apart from parent personality and child temperament, other factors that influenced parenting styles were parenting stress, which arises when parenting demands exceed the actual resources available to parents; a history of abuse in parents in their childhood; and parent’s attachment style, self-efficacy, perfectionism, etc. Perhaps, future studies on parenting can include these variables for a better understanding of parenting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In explaining the above results, it can be stated that authoritative parenting styles is the most effective parenting style in supporting students' self-efficacy and actually psychological wellbeing of students. With authoritative parenting style, students are given opportunity to discuss matters and decisions with their parents (Vafaeenejad et al, 2019;Walton et al, 2018;Alnafea & Curtis, 2017;Masud et al, 2016;Kuppens & Ceulemans, 2019;Hoang, 2007). This develops students autonomy, positive self-concept and belief (Kuppens & Ceulemans, 2019).…”
Section: Discussionmentioning
confidence: 99%